Characterization and validation of an isotope-dilution LC–MS/MS method for quantification of total desmosine and isodesmosine in plasma and serum. (August 2013) - Albarbarawi, Osama; Barton, Alun; Miller, Douglas; McSharry, Charles; Chaudhuri, Rekha; Thomson, Neil C; Palmer, Colin NA; Devereux, Graham; Huang, Jeffrey T-J
Background: Desmosine/isodesmosine (DES/IDS) is a promising biomarker for estimating activity of elastin degradation.Results/methodology: A stable isotope dilution LC–MS/MS method for measuring serum/plasma DES/IDS was developed and validated. The reportable range of this assay was 0.1–160 ng/ml. Serum/plasma DES/IDS level was stable at room temperature or 4°C for 20 h, and for three freeze–thaw cycles. Interferences from endogenous compounds and ion suppression/enhancing effect were also evaluated. Our results suggest the absolute necessity of using an IS in the measurement. We found that serum/plasma DES/IDS levels from patients with chronic obstructive pulmonary disease and cystic fibrosis were significantly higher compared with healthy smokers.Conclusion: These results demonstrate that the LC–MS/MS method provides sensitive, reproducible and accurate quantification of total serum/plasma DES/IDS.